PENERAPAN PEMBELAJARAN MATEMATIKA BERBASIS PENDEKATAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 5 DI SDN 04 KLEGEN BERBANTUAN MEDIA PPT DAN PROYEK KARYA VISUAL - Melani Dyah Puspita; Marsda Nur Ramadhanni; Reni Puspitasari; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Through the use of the Project Based Learning learning model, this study aims to improve the mathematics learning outcomes of Class V students in the second semester of SDN 04 Klegen in the 2024/2025 academic year. The type of implementation of this research is Classroom Action Research. The subjects of this study were 9 students from Class V SDN 04 Klegen, including three female students and six male students. The focus of this study is students' mathematics learning outcomes. The use of the learning outcome test method is used to collect learning outcome data which is then evaluated descriptively. Student learning outcomes that reach ≥ 70 with learning completeness ≥ 85% are used as indicators of success in this study. Based on the results of the study, the average value of students' mathematics learning outcomes in cycle I was 73.33 with classical completeness of 77.8% and in cycle II the average value reached 90 with classical completeness of 100%. Based on the results of this study, it shows that in the 2024/2025 academic year, the Project Based Learning learning model can improve mathematics learning outcomes in the flat geometry material of class V students, semester II of SDN 04 Klegen. Through the use of the Project Based Learning learning model, this study aims to improve the mathematics learning outcomes of Class V students in the second semester of SDN 04 Klegen in the 2024/2025 academic year. The type of implementation of this research is Classroom Action Research. The subjects of this study were 9 students from Class V SDN 04 Klegen, including three female students and six male students. The focus of this study is students' mathematics learning outcomes. The use of the learning outcome test method is used to collect learning outcome data which is then evaluated descriptively. Student learning outcomes that reach ≥ 70 with learning completeness ≥ 85% are used as indicators of success in this study. Based on the results of the study, the average value of students' mathematics learning outcomes in cycle I was 73.33 with classical completeness of 77.8% and in cycle II the average value reached 90 with classical completeness of 100%. Based on the results of this study, it shows that in the 2024/2025 academic year, the Project Based Learning learning model can improve mathematics learning outcomes in the flat geometry material of class V students, semester II of SDN 04 Klegen.